Implicit and Explicit Deposit Insurance and Depositor Behavior - Sümeyra Atmaca; Karolin Kirschenmann; Steven Ongena; Koen Schoors (Center for Economic Studies and ifo Institute (CESifo), 2023)
We employ proprietary data from a large bank to analyze how – during crisis – deposit insurance affects depositor behavior. Our focus is on Belgium where the government increased explicit deposit insurance coverage and implemented implicit deposit insurance arrangements. Estimating sorting below the respective insurance limits shows that depositors are aware of and understand these interventions. Difference-in-differences estimates show that both the increase in the explicit deposit insurance limit and the implicit deposit insurance had the intended calming effect on depositors. Close depositor-bank relationships mitigate these effects, while political trust seems to boost the general effectiveness of such government policies.
Keywords: G21; G28; H13; N23; 330; deposit insurance; coverage limit; implicit deposit guarantee; bank nationalization; depositor heterogeneity